Women Empowerment and Opposition Political Parties in Africa: Efforts Towards Achieving Sustainable Development Goals (SDGs) - CHUKWUDI, Celestina Ekene; Eneanya, Augustine Nduka; OLADIPO, Temidayo David; Osimen, Goddy Uwa (Journal of Ecohumanism, 2024)
This study is to explore different ways that opposition political parties have adopted towards the political empowerment of women in African society to ensure their well-being which is part of Sustainable Development Goals (SDGs) number three (3) of United Nations Agenda 2030. The study is also out to explore the challenges facing the empowerment of women thereby disrupting their supposed contributions to the development of politics in general and political parties in particular within Africa. This study adopts qualitative research methods in the source for information which is secondary data. The sourced information is obtained from textbooks, Journals and conference publications, Newspapers, Magazines, and reliable internet materials. The theoretical framework adopted in this study is Liberal Feminism. The finding reveals opposition political parties do not have more political, economic, and social strength than the ruling political party in empowering the women, but they adopt different strategies that can help them to mobilize the women population. They do these by creating an acceptable quota system for women in their party leadership, creating women’s wings, and economic development, reducing the cost of tickets for women, and raising funds for training and sponsoring women in political positions.The study concludes that opposition political parties have less of the needed political and economic strength to fully empower women and achieve their expected well-being as they lack control over the nation’s policies and adequate resources.